2016
DOI: 10.1097/wco.0000000000000315
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system neuroinflammatory disorders in Asian/Pacific regions

Abstract: The understanding of CNS neuroinflammatory disorders in Asian/Pacific regions continues to evolve owing to the discovery of new biological markers and recognition of broader clinical phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 130 publications
(150 reference statements)
0
13
0
Order By: Relevance
“…A study conducted in Australia and New Zealand showed that NMOSD was three times more prevalent in individuals with Asian ancestry than in the remaining population with predominantly European ancestry ( 9 ). In addition, the NMOSD/multiple sclerosis ratio has been reported to be higher in Asia than in Western countries ( 10 ). A recent study using data from a large international cohort of adult patients with NMOSD revealed that race affected the clinical phenotype, age at onset, and severity of attacks, but the overall clinical outcome was most dependent on early and effective immunosuppressive treatment initiation ( 11 ).…”
Section: Review Of Current Knowledgementioning
confidence: 99%
“…A study conducted in Australia and New Zealand showed that NMOSD was three times more prevalent in individuals with Asian ancestry than in the remaining population with predominantly European ancestry ( 9 ). In addition, the NMOSD/multiple sclerosis ratio has been reported to be higher in Asia than in Western countries ( 10 ). A recent study using data from a large international cohort of adult patients with NMOSD revealed that race affected the clinical phenotype, age at onset, and severity of attacks, but the overall clinical outcome was most dependent on early and effective immunosuppressive treatment initiation ( 11 ).…”
Section: Review Of Current Knowledgementioning
confidence: 99%
“…We estimated the pooled AQP4-IgG and MOG-IgG prevalence in isolated ON separately for Asian and non-Asian populations, given the divergence of prevalence between studies in these populations, and evidence supporting higher prevalence of NMOSD in Asian populations ( 10 ). Given the relatively low prevalence of these disorders in some of the included studies (estimates close to 0%), we utilized the variance-stabilizing double arcsine transformation method ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…In patients presenting with classic neuromyelitis optica (NMO) or acute disseminated encephalomyelitis (ADEM)-like phenotypes, clinical suspicion for AQP4-IgG- or MOG-IgG-associated disease is high, but diagnosis may be challenging and delayed in limited forms, such as isolated ON. Notably, the reported prevalence of AQP4-IgG and MOG-IgG seropositivity among patients presenting with isolated ON varies significantly between studies, and the available literature suggests that seropositivity for these antibodies is more common in non-white populations with ON ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…4 The NMOSD/ multiple sclerosis ratio is reported to be higher in Asia than in Western countries. 5 Therefore, comparative studies across different races are needed to determine whether the epidemiologic differences observed reflect true racial differences in the NMOSD phenotype and prognosis.…”
mentioning
confidence: 99%